Combining opensource GIS and meta-analysis to link rainfall trend and human activity: case study on Gumti and Khowai drainage systems, Tripura, India - Majumdar, Sima; Das Pan, Nibedita (Spatial information research (Online), 2020)
Analysis of rainfall trend may help to identify local and regional critical control factors that regulate rainfall pattern. Oscillation in the local trend may be governed by global events like climate change. Moreover, regional level trend analysis of climatic factors would divulge the mechanism of interplay between the impact of climate change and the effect of local phenomena like human activity. Therefore trend analysis of decadal rainfall time series (2001–2010) over 2 major rivers of Tripura coupled with a GIS based spatio-temporal simulation of the region was done. Regression model of the smoothen rainfall time series revealed clear decline for both rivers (y = −0.6793x + 243.99 and y = −0.1792x + 193.68 for Khowai and Gumti respectively). A systematic meta-analysis of meteorological reports for the period 1871–2017 was done to generate a collective climatic conscience of the region in tabular form, that also ascertained decreasing rainfall trend. This study may aid to pin point the specific regional factors that impact rainfall, which is in contrast to the general circulation models that only focus on global events in a very large area. Land use pattern, land cover changes and under developed agriculture practices are some anthropogenic factors that may be accounted for steady decrease of monsoon rainfall leading to man-made climate change.